ANALISIS SOLIDARITAS SOSIAL MEKANIK PADA ETNIS MADURA DAN MELAYU DI KELURAHAN SIANTAN TENGAH KECAMATAN PONTIANAK UTARA - Jumiliani Jumiliani; Fatmawati Fatmawati; Iwan Ramadhan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTThis study aims to determine the social mechanical sosilidarity of the Madurese and Malay ethnicities in Siantan Tengah Village, North Pontianak District. The general problem in this research is "How is the analysis of mechanical social solidarity on ethnic Madurese and Malays in Siantan Tengah Village, North Pontianak District". The research method used is descriptive in a qualitative form. Data collection techniques using observation, interviews, documentation. The data collection tools used were observation guidelines, interview guidelines, and documentation guidelines. The data analysis in this study was presented in a qualitative descriptive manner using 4 informants of Madurese and Malay ethnicities in Siantan Tengah Village, North Pontianak District. The results of this study indicate that Madurese and Malay ethnicities can mingle with each other and have a high level of solidarity, and can foster a sense of care for fellow humans and the environment, a sense of empathy, a sense of being helped, a sense of sincerity in helping, a sense of brotherhood, a sense of peace, a sense of Tolerance, respect, familiarity, and affection for fellow communities or relatives can be seen from the division of labor, strong collective awareness, and low individuality in Siantan Tengah Village, North Pontianak District.Keywords: Ethnic Malay, Madurese Ethnicity, Mechanical Solidarity